2008
DOI: 10.1002/pd.2027
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of superimposed preeclampsia using uterine artery Doppler velocimetry in women with chronic hypertension

Abstract: The later in pregnancy the abnormal UtA Doppler findings are observed, the greater the risk of preeclampsia. Normalization of UtA Doppler after 25 weeks reduces the risk of preeclampsia to 8%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…Placental invasion is indeed a progressive process, as supported by pathological studies14 and by the gradual fall in uterine artery pulsatility throughout gestation15. Nevertheless, the fate of those who are late normalizers has been subjected to only a few studies5, 6, 16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Placental invasion is indeed a progressive process, as supported by pathological studies14 and by the gradual fall in uterine artery pulsatility throughout gestation15. Nevertheless, the fate of those who are late normalizers has been subjected to only a few studies5, 6, 16.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, how to manage pregnant women if abnormal uterine Doppler is detected in the mid‐trimester is controversial. A reassessment of the uterine circulation later in these pregnancies has been suggested5, 6. It was recently reported that the sequence of changes in uterine flow between the first and second trimesters correlates with the subsequent development of hypertensive disorders and IUGR7.…”
Section: Introductionmentioning
confidence: 99%
“…The exact pathophysiological mechanism through which SLE induces placental damage, possibly leading to PE, is unknown . However, second trimester UtA Doppler prediction of PE has been described to be particularly valuable in pregnancies at high risk of PE due to pre‐existing medical conditions . Despite an increasing and promising move toward the first trimester screening of PE in the general pregnant population, such approach seems less promising in women with high‐risk conditions who would nevertheless already be candidates to intensive monitoring of pregnancy and LDA administration.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have studied the predictive role of first trimester UtA Doppler velocimetry both in high risk and unselected populations . Plasencia et al .…”
Section: Discussionmentioning
confidence: 99%